Parental practices and beliefs on motor development in the first year of life - Alcilene Maria Gomes; Rayane Fonseca Ribeiro; Bernat Vinolas Prat; Lívia de Castro Magalhães; Rosane Luzia de Souza Morais
Abstract Introduction: In the child's first year of life, motor development is critical for the other areas of child development. Beliefs and parenting practices influence the parents' care and encouragement of their children, reflecting in their motor development; however, the Brazilian literature on this subject is scarce. Objective: to characterize the parental practices and beliefs associated with motor development in the first year of life; and to verify if practices and beliefs are interrelated. Methods: Two questionnaires were developed and applied, one about parenting practices and the other about parental beliefs on motor development in the first year life, to 27 caregivers of children between 12 and 24 months of age, who participated in an aquatic stimulation program. The agreement between practices and beliefs was verified by a graphical method, based on the transformation of ordinal scores to an interval scale using Rasch analysis. Results: The participants had higher levels of education and economic status. They reported a variety of practices focused on the motor development of their children, such as family interaction through playing, toy offers, lap time and free movement space. Conclusion: Most of the practices were based on parental beliefs, for some activities, however, beliefs and practices diverged, demonstrating the complexity inherent to the formation of parental beliefs.